(untitled) (Per Musi, 2023)
SIX-XEN, the acoustic instrument created by Iannis Xenakis for Pléïades (1978), is representative of the composer’s creative process and his interest in percussion. The creator’s own descriptions, as well as the connections between the object and his theoretical and practical work, shed light on structuring and fundamental aspects of the conceptual and sonic universe of Xenakis’ research. These aspects can be observed through different documents: initial sketches, manuscripts, different editions of Pléïades, letters, personal notes and interviews. As an object created by a composer, the instrument has characteristics that are a direct reflection of its creator’s practical and aesthetic approaches. Taking this into consideration, this article addresses the Xenakian percussive instrument with an emphasis on: microtonality, acoustic beat, glissando and variability through non-faithful repetitions. In creating the SIX-XEN, Xenakis entrusted the percussionist community with an enormous responsibility because the research and the construction of prototypes are constant challenges in order to play his piece.